Malaria in China: a discourse-historical perspective - Miao, Peng (Frontiers in Medicine, 2025)
The translation, transmission, and re-conceptualization of malaria in late Qing and Republican China exemplifies how knowledge on an ancient disease is reshaped through linguistic and cultural mediation. This article analyzes diverse textual medical sources, namely English-Chinese dictionaries (1830s-1900s) and vernacular newspapers and periodicals, to trace and observe the lexical journey of “ague” and “malaria” into the Chinese domain as “nueji” (瘧疾/疟疾) and “zhangqi” (瘴氣/瘴气). Three phases of conceptual transfer are identified: first, early missionary dictionaries (1822–1860s) prioritized symptom-based translations (e.g., faleng 發冷/发冷, chills); second, the 1870s-1920s witnessed terminological competition between nueji and zhangqi, reflecting clashes between traditional Chinese etiology and western theories; third, by the 1930s-1940s, nueji became dominant through institutional standardization, while western parasitological frameworks were selectively assimilated, as “Plasmodium” was lexicalized as “nueyuanchong” (瘧原蟲/疟原虫), yet the mechanism of “immunity” remained unexplained in Chinese medical discourse. This process was formed by intra-medical debates: while western-trained practitioners weaponized microscopy to validate Plasmodium as a pathogen, traditional healers reframed it through local cosmology. Newspaper and periodicals served as contested epistemic spaces, where terms like “weichong” (微蟲/微虫) and “jishengchong” (寄生蟲/寄生虫) mirrored public struggles to reconcile western knowledge with local beliefs. This article demonstrates that disease introduction transcends lexical substitution, acting as a battlefield for different medical discourses in China’s medical modernization.